Synthesis of Religion and The State - Asriani, Asriani (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
The discussion between the relationship between religion and the state never stops being debated and it is difficult to find points of common ground, because each considers the conception offered to be correct and very appropriate for every condition of the times. Islam in general. This is because almost all the figures and scholars who are used as references with their various arguments are inseparable from the three models of state that currently exist in the Islamic world, namely: Islamic, Secular, and Muslim. Even though there are differences between the three, this substantially boils down to one of these state models. In principle, the relationship between religion and the state in general can be polarized into two parts. both. Second, the theocentrism (fundamentalism) group which considers religion and the state cannot be separated, in fact there is not even a single space in this world, including the state which is allowed to be free from religious constraints. However, the development of both (religion and state) is very much determined by human belief.Based on the description above, the writer is interested in studying the relationship between religion and the state. Keywords: relation, religion, country